Thermal and tribological properties enhancement of PVE lubricant modified with SiO2 and TiO2 nanoparticles additive - Azmi, Wan Hamzah; Ismail, Mohd. Farid; Mamat, Rizalman; Hafiz Muhammad Ali (MDPI, 2023)
The addition of nanoparticles may have a positive or negative impact on the thermal and tribological properties of base lubricant. The objective of this paper is to investigate the effect of nanoparticle dispersion in lubricant base in relation to its application in refrigeration system compressors. An investigation of tribological and thermal properties of nanolubricants for rolling piston rotary systems was carried out through four-ball tribology tests and thermal conductivity measurements. Nanolubricants dispersed with SiO2 and TiO2 nanoparticles were tested at various concentrations and temperatures. The changes in thermal conductivity and coefficient of friction (COF) were analyzed while wear weight loss was also calculated from wear scar size. A regression model of thermal conductivity enhancement was proposed for both types of nanoparticles. Zeta potential results show that nanolubricants have excellent stability. The thermal conductivity increases by the increment of nanoparticle concentration but decreases by temperature. The R-square for the regression model is more than 0.9952 with an average deviation not more than 0.29%. The COF for SiO2/PVE nanolubricant at 0.003 vol.% reduced 15% from the baseline. The COF for nanolubricants exceeds the result for base lubricants when the concentration is more than the threshold value. The optimum concentration of SiO2 and TiO2 nanoparticles improved the thermal and tribological properties of PVE lubricant and may offer an advantage when applied to refrigeration systems.